Risk profile of coronary heart disease among the staff members of Qassim University, Saudi Arabia - Alnohair, Sultan; ALMohaimeed, Abdulrahman; Sharaf, Fawzy; Naeem, Zahid; Midhet, Farid; ALHomaidan, Homaidan; Winter, Sandra J (International Journal of Health Sciences, 2017)
Objective: To estimate the risk profile of coronary heart disease among the staff members of Qaasim University and assess their knowledge in a screening campaign in Qassim Region, Saudi Arabia. Methodology: A cross-sectional study was conducted among male & female staff at Qassim University campus. All employees of Qassim University were invited to participate in the study. Data were collected through a self-administered questionnaire. The study sample size was 233 staff and employees. The data were entered and analyzed by using SPSS version 18. The data analysis focused on providing point estimates for the risk factors. Results: The study found that 30% of participants have one or more risk factors for CHD, namely Obesity 20.6%, Diabetes 10.3%, Hypertension 12.4%, Dyslipidemia 10.7% and smokers (11.6%). About 54% of the participants have a family history of at least one chronic disease as a risk factor for CHD. Conclusion: The most common risk factor of coronary heart disease among the staff members is obesity by 20.6 %. Risk factors for coronary heart disease are quite common among Qassim University staff. These finding need to Increase the health education and disease promotion program as an important intervention to reduce the occurrence and severity of coronary heart disease risk factors and to improve the quality of the life of the staff members of Qassim University.